Peat ground improvement with GeoPolySoilS - Ismacahyadi Bagus Mohamed Jais,; Muhammad Luqmanul Haqim Mustafa Kamal,; Diana Che Lat, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Peat soil is frequently seen as a soil foundation concern which normally required soil stabilization work. This study is conducted to assess the strength of peat soil mixed with GeoPolySoilS as a proposed ground improvement work for peat soil in Kampung Johan Setia in Klang Selangor, Malaysia. In order to look into the strength improvement of this peat soil, laboratory tests were conducted namely Unconfined Compressive Strength Test (UCT) and Calfornia Bearing Ratio Test (CBR). The highest strength of UCT for the uncured soils with 14% GeoPolySoilS is 161 kPa whilst for the sample that was cured for 7,14,28 and 50 days, the highest value of UCT with 20% GeoPolySoilS are 58.08 kPa,61.66 kPa, 95.62 kPa and 80.04 kPa respectively. For the CBR value, the highest top layer value is 8.12% for peat soil mixed with 14% GeoPolySoilS whilst the highest value for the bottom layer is 62.25% for unsoaked CBR. For soaked CBR, the highest top layer value is 5.82% for 20% GeoPolySoilS and the highest value for bottom layer is 43.07%. The strength of the modified peat increased with the increased of curing time and the percentage of GeoPolySoilS